Pelatihan Penulisan dan Publikasi Artikel Penelitian Tindakan Kelas di Jurnal bagi Cendekiawan Pendidikan - Imam Rofiki; Dwi Setiawati Radjak; Mudjia Rahardjo; Winarno (Institute for Research and Community Services, 2024)
Understanding and having the skills for conducting Classroom Action Research (CAR) or Penelitian Tindakan Kelas (PTK) for educators and prospective educators are still inadequate, due to lack of knowledge in writing and publishing in national journals. This service aims to provide training in writing and publishing PTK articles in national and international journals for educational scholars. Service activities are carried out in the form of online training, involving 78 educational scholars throughout Indonesia, in a national seminar initiated by the Research Training Institute